2010
DOI: 10.1371/journal.pone.0012030
|View full text |Cite
|
Sign up to set email alerts
|

The Native Copper- and Zinc- Binding Protein Metallothionein Blocks Copper-Mediated Aβ Aggregation and Toxicity in Rat Cortical Neurons

Abstract: BackgroundA major pathological hallmark of AD is the deposition of insoluble extracellular β-amyloid (Aβ) plaques. There are compelling data suggesting that Aβ aggregation is catalysed by reaction with the metals zinc and copper.Methodology/Principal FindingsWe now report that the major human-expressed metallothionein (MT) subtype, MT-2A, is capable of preventing the in vitro copper-mediated aggregation of Aβ1–40 and Aβ1–42. This action of MT-2A appears to involve a metal-swap between Zn7MT-2A and Cu(II)-Aβ, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…MTs bind copper with high affinity, suggesting a role in copper homeostasis (Chung et al, 2008, 2010), and mice displaying copper overload crossed with an MT 1/2 knockout did not survive past infancy (Kelly and Palmiter, 1996). Exchange between protein and metal has been observed in studies that found MTs prevented copper-induced aggregation of amyloid beta peptide or alpha-synuclein (Meloni et al, 2008; Meloni and Vašák, 2011; De Ricco et al, 2015b).…”
Section: Metallothioneinsmentioning
confidence: 99%
“…MTs bind copper with high affinity, suggesting a role in copper homeostasis (Chung et al, 2008, 2010), and mice displaying copper overload crossed with an MT 1/2 knockout did not survive past infancy (Kelly and Palmiter, 1996). Exchange between protein and metal has been observed in studies that found MTs prevented copper-induced aggregation of amyloid beta peptide or alpha-synuclein (Meloni et al, 2008; Meloni and Vašák, 2011; De Ricco et al, 2015b).…”
Section: Metallothioneinsmentioning
confidence: 99%
“…This provides an estimated average Cu I affinity for MT‐2A of 2.4×10 15 m −1 and positive cooperativity with a Hill coefficient of ≈4 (the value for Mt Csp1 is around 3) . A very similar average Cu I affinity has been measured for MT‐3 (2.1×10 15 m −1 ), but in this case Cu I binding shows only weak positive cooperativity (Hill coefficient of 1.3) . These Cu I affinity measurements only considered the 1:1 Cu I :DTT complex, as previously discussed, resulting in values being underestimated by as much as 3–4 orders of magnitude.…”
Section: Bacterial Copper Storage Proteinsmentioning
confidence: 99%
“…Furthermore, it is able to influence the response of both neurons and glial cells, and it may also have an effect on immune system cells. For example, MT promotes regenerative neuronal growth after injury (Chung et al 2003) and separately, it improves neuronal survival in the face of a variety of neurotoxic insults (Ambjorn et al 2008) – for example, following Aβ administration (Chung et al 2010). MT appears to do this by stimulating receptors of the lipoprotein receptor-related protein (LRP) family and triggering a pathway involving Erk1 and CREB activation (Ambjorn et al 2008).…”
Section: Endogenous Neuroprotective Molecules (Akw Gjg)mentioning
confidence: 99%